Introduktion til Danne- Virke. I - Michelsen, William (Grundtvig-studier, 1985)
Introduction to Danevirke I By William Michelsen. Grundtvig never wished to give a systematic presentation of his philosophy. He was a historian, and as such he realised that we only know the development of human life up to our own time and that no man has experienced its origin. A systematic presentation of human life would presuppose a knowledge which we do not possess. However, in his periodical Danevirke (1816-19) he does offer a number of “considerations of human life in general”, as he writes in the preface to its final volume, and it is on this foundation that his later thoughts rested.These considerations, which at first he called “papers”, were not republished in full until 1983. The beautifully-photographed reproduction of the entire work, published in the bicentenary year by J.rn Bergmann (AKA-print, .rhus), is thus the most important document for Grundtvig research of all the many publications in 1983.The periodical, which includes both poetry and prose of various content, was written by Grundtvig alone, in the same period which saw the publication of Prospect of World Chronicle Especially in the Age of Luther and the start of his translation of the medieval historians, Saxo and Snorri. Danevirke contains his first contributions to Beowulf research, his evaluation of the poets Baggesen and Oehlenschl.ger, and his dramatic poem, The Easter Lily, on the resurrection of Jesus. It is worth noting that Grundtvig’s criterion for true Christianity in the period 1810-25 is still the same as Luther’s: the holy scripture. His assessment of the relationship between religion, politics and scholarship (“ Church, State and School”) changed in 1832 to a demand for “ Freedom in Spiritual Things”. This did not, however, alter his view of man as it appears in Danevirke. The present and future articles contribute to an understanding of this.In preparation for these reflections Grundtvig wrote Grenzen der Menschheit, which was published in Grundtvig Studies 1984. An interpretation of this manuscript relates Grundtvig to Schelling’s philosophy. Grundtvig here asks the questions: What is my I? and: Is the true answer idealistic or materialistic? Grundtvig rejects both possibilities. Man cannot apprehend absolute being. In contrast to an idealistic view of man Grundtvig presents the Christian view: man is created from dust, and animated by God’s spirit - not a philosophical view but a religious one, interpreted in the gospel of John. Jesus’s appearance as the Son of Man was a repetition of the creation of man as depicted in Genesis 1 - 2. According to the Bible man is eternal and divine through the power of the living word, which is God’s creative Word. It is therefore untrue of Schelling to assert that man is created by “the idea everlasting”, which to him means, by man’s idea of God. This is a refusal to see man created in God’s image but only God created in man’s image, “an image of what is Nothing”. Without the divine creative Word, man is no more than transient body. Yet Schelling has understood the relationship between the temporal and the eternal. He has presented the riddle of human life, but he has not solved it. It is an illusion to believe that natural philosophy has solved it, and foolish to regard the gospel as a prophecy of natural philosophy. If that were so, then one would have to demand that it had as great an effect as the gospel of Jesus has actually had. But in Grundtvig’s opinion it has had as little effect as the philosophy of the gnostics in antiquity.It was not Grundtvig’s intention, however, to take part in the contemporarydebate on philosophy. By 1816 Schelling’s ideas were no longer dominant in German philosophy, and Hegel’s were not introduced to Danish philosophy until 1825 by J. L. Heiberg. Grundtvig’s aim was rather to formulate his alternative to the idealist German philosophy. That was the purpose of Danevirke. But it also had another purpose.To be Danish without being Norwegian was a new feeling for Grundtvig in 1816. In his programme On Danish Poetry, Language and History he refers to the Danes’ love of their language and their unwillingness to extend their country beyond its ancient borders. He thus deduces the concept of Danishness from the language and the historical sources. He sets out to spread knowledge of these by publishing works from the middle ages with commentaries and by translating Icelandic manuscripts. He protests against a human philosophy that ignores linguistic and national differences in literature and history. But in so doing he does not deny either his Christianity or his love for the rest of the North. On the other hand, he rejects the cosmopolitan human philosophy of the 18th century as derived from the century’s philosophical systems from Christian Wolf to Schelling. Schelling clearly belongs to the philosophers he rejects, and Kant and Fichte must now be counted alongside.